PENGARUH STANDAR AKUNTANSI PEMERINTAHAN, SISTEM INFORMASI AKUNTANSI DAN KOMPETENSI PENGELOLAAN KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN - Irsan, Muhammad (SEKOLAH PASCASARJANA PRESS, 2019)
This study aims to determine the effect of government accounting standards, accounting information systems, financial managers competence on the quality of financial statements (an empirical study on the implementation of the directorate general of Hajj and Umrah Ministry of Religion). Population and sample involved 238 respondents. This study uses statistical analytics with SPSS 23 and multiple linear equations. Based on the results of testing whole hypothesis, this study shows that simultaneously independent variables of government accounting standards, accounting information system, the competence of financial managers positive significant effect on the quality of financial statements. While in partial goverment accounting standards have a significant influence on the quality of financial statements, accounting information system have a significant influence on the quality of financial statements, the competence of financial managers did not have a significant impact the quality of financial reporting.